Robust stability and stabilization analysis for discrete-time randomly switched fuzzy systems with known sojourn probabilities. (August 2015) - Jarina Banu, L.; Balasubramaniam, P.
Abstract: The stability and stabilization analysis problem is considered in this paper for a class of discrete-time switched fuzzy systems with known sojourn probabilities. By using Lyapunov functional, new delay-dependent sufficient conditions are derived to ensure the stability of the system. Convex combination technique is incorporated and the stability criteria are presented in terms of Linear matrix inequalities (LMIs). Furthermore, the developed approach is extended to address the robust stability and stabilization analysis of the delayed discrete-time switched fuzzy systems with randomly occurring uncertainties. Finally numerical examples are exploited to substantiate the theoretical results.